ALDOSTERONE RECEPTOR ANTA-GONISTS: CLINICAL PHARMACOLOGY AND THERAPEUTIC EFFICIENCY IN CHRONICAL HEART FAILURE - Bilovol, A.N.; Knyazkova, I.I. (World of Medicine and Biology, 2012)
In the review іt is marked, that additional assignment of aldosterone receptor antagonists to standard therapy improves survival rate of patients with heavy HF type and left ventricle dysfunction after myocardial infarction. Thus the dynamic control of clinical and biochemical parameters of the patient is obligatory. Close adherence to these recommendations will promote increase of efficiency and decrease drug side effect of aldosterone receptor antago¬nists.
Keywords: heart failure; aldosterone receptor antagonists